A Study of Acoustic Parameters of Transformer Oil Based on Its Water Content Utilizing a Single Ultrasonic Sensor - Firnanda Pristiana Nurmaida; Agus Indra Gunawan; Raden Sanggar Dewanto (Advances in Technology Innovation, 2024)
The health of a transformer is affected by several aspects, including water content in transformer oil. Researchers have introduced various techniques for measuring water content in transformer oil. In the case of acoustical measurement, researchers typically utilize two ultrasonic sensors to detect acoustical parameters. This study proposes a novel technique to characterize transformer oil based on its water content using a single ultrasonic sensor. This technique employs an indirect measurement approach, where a substrate separates the oil from the sensor. The echoes from measurements are observed and presented in terms of three acoustical parameters, i.e., the acoustic speed, acoustic impedance, and density. Based on measurement results, the acoustic speed of the samples is successfully calculated from the time of flight. and the thickness of the chamber. However, only four materials used as substrate 1, i.e., 3mm, 5mm, 8mm acrylic, and 3mm glass, successfully produce similar plots of acoustic impedance and density.